Crystal packing control of a trifluoromethyl‐substituted furan/phenylene co‐oligomer. Issue 5 (19th September 2018) - Sonina, Alina A.; Koskin, Igor P.; Sherin, Peter S.; Rybalova, Tatyana V.; Shundrina, Inna K.; Mostovich, Evgeny A.; Kazantsev, Maxim S.
Abstract : Trifluoromethyl substituents control the crystal packing and optical properties of a furan/phenylene co‐oligomer. All obtained crystals are highly emissive; however, their photophysical properties strongly depend on the crystal packing. Abstract : Furan/phenylene co‐oligomer single crystals are considered as future materials for organic optoelectronics. Here, the effects of trifluoromethyl substituents on the crystallization, structure and optical properties of furan/phenylene co‐oligomer 1, 4‐bis5‐[4‐(trifluoromethyl)phenyl]furan‐2‐ylbenzene are studied systematically. The solution growth methods and physical vapor transport result in the formation of three polymorphs depending on the growth method and the solvent. Single‐crystal X‐ray analysis reveals the crystal structures to correspond to H‐, J‐ or mixed aggregates. All obtained crystals exhibit high photoluminescence efficiency and have optical properties which strongly depend on the crystal packing. Variable‐temperature X‐ray powder diffraction analysis shows the thermal transition of two forms (H‐ and J‐aggregates) into a third one (mixed aggregate). Terminal trifluoromethyl groups induce weak intermolecular interactions which control the crystal packing and optical properties of co‐oligomer single crystals.